1954
DOI: 10.1107/s0365110x54000011
|View full text |Cite
|
Sign up to set email alerts
|

Röntgenographische Strukturuntersuchungen hexagonaler Einschlussverbindungen des Thioharnstoffs

Abstract: The ground structure of thiourea in adduct compounds of thiourea belongs to the space group R'32/c with a ~ 15.8, c ~ 12.5 ttx. The thiourea molecules have the same shape as in the orthorhombic thiourea and their parameters are xs ----0.2995; xc = 0.414; xN = 0.444, yN = --0.014, zN = 0.086.Cyclohexane as an adduct is situated near the sulphur atoms within the canal or tube formed by the thiourea molecules.Most parts of the diffraction pattern can be assigned either to the ground substance or to the enclosed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…A completely analogous phenomenon was also found for thiourea; in this case the structure determination is due to LENN^ (1954). The basic structure has a similar honeycomb form, but the symmetry is reduced, the space group now being the rhombohedral R3c.…”
Section: Introductionmentioning
confidence: 55%
“…A completely analogous phenomenon was also found for thiourea; in this case the structure determination is due to LENN^ (1954). The basic structure has a similar honeycomb form, but the symmetry is reduced, the space group now being the rhombohedral R3c.…”
Section: Introductionmentioning
confidence: 55%
“…[1][2][3][4] In host subunit, thiourea molecules are mutually linked by hydrogen bonds so as to build channels arrayed like a honeycomb. [5][6][7][8] Guest molecules are embedded one-dimensionally inside the channels with diameter varying from 5.5 to 7.1 # A depending upon their sizes and shapes. 9) For the guest molecules with nearly spherical shape, thiourea inclusion compound is rhombohedral at room temperature and, in most case, transforms to a monoclinic phase at lowtemperature.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods such as solvent evaporation, 1) grinding, 2,3) and slurrying 4) are used to prepare cocrystals, and changes in solubility 5,6) and improvement in physical stability 7) and bioavailability 8) as a result of the formation of cocrystals have been studied. Thiourea (TU) forms inclusion complexes with guest molecules in a tunnel structure, 9) and TU is used to isolate and purify substances. Like TU, urea forms inclusion complexes with a tunnel structure, 9) and a study has reported improving its solubility of guest molecules and improving its stability to light.…”
mentioning
confidence: 99%
“…Thiourea (TU) forms inclusion complexes with guest molecules in a tunnel structure, 9) and TU is used to isolate and purify substances. Like TU, urea forms inclusion complexes with a tunnel structure, 9) and a study has reported improving its solubility of guest molecules and improving its stability to light. 10) One difference between TU and urea is that TU inclusion complexes have a tunnel structure with a larger inner diameter than that of urea inclusion complexes.…”
mentioning
confidence: 99%